The effect of psychological moods, serum cortisol and comt polymorphism towards academic achievement among female undergraduate students in UiTM / Hazirah Abd Azhar - Abd Azhar, Hazirah (2020)
The psychological health among undergraduate students has gained wide attention from society. Yet, only a few studies examined the psychological health of undergraduate students along their study period of a semester. The aim of this study is to determine the effect of psychological moods and genetic polymorphism towards academic achievement among female undergraduate students in UiTM. This study used a follow-up study design to determine the levels of depression, anxiety, stress, perceived stress and the concentration of cortisol and cortisone at three different time points in a semester which are the beginning of the semester (TP1), the middle of the semester (TP2) and the final examination week (TP3). A total of 52 female undergraduate students from Universiti Teknologi MARA Selangor Branch, Puncak Alam Campus, were administered with the Depression, Anxiety and Stress Scale (DASS) questionnaire consisting of 42 questions to assess the depression, anxiety and stress levels and 11 questions of Perceived Stress Scale (PSS) questionnaire to determine the perceived stress level. The serum cortisol level was determined using a validated Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) method. The COMT polymorphism were determined using an in-house tetra-primer PCR method. The data were analysed using Paired sample t-test, Pearson Correlation, MANOVA test and Backward Multiple Regression analysis using SPSS software. This study demonstrated that female undergraduate students experienced the highest level of psychological mood problems during the middle of the semester. There was a significant increase in depression, anxiety, stress, perceived stress and cortisol levels from TP1 to TP2. The COMT polymorphism showed no association with any of the psychological mood parameters. Multiple regression showed that out of all psychological mood variables studied, only stress level as measured using DASS questionnaire and perceived stress level as measured using PSS questionnaire showed statistically significant results in predicting students’ academic achievements. This study provides empirical evidence that high stress level as measured using DASS promotes better academic achievement while perceived stress as measured using PSS was predicted to give a negative outcome in academic performance. This research suggests that addressing these levels of psychological health are important in helping the students to improve their quality of life.